Penyuluhan Perawatan Kaki Pada Lansia Dengan Diabetes Mellitus Tipe Ii Di Puskesmas Kalijaga Permai Cirebon - Ainun Kurniati; Haeril syafrudin (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
This activity aims to provide health education to the elderly about foot care to prevent injuries. Through lecture methods, question and answer, and demonstrations. Implementation of community service in providing counseling to people with diabetes mellitus as an effort to increase knowledge about foot care by changing attitudes, behavior and increasing compliance in foot care for the elderly. The counseling started with foot care for the elderly, then continued with foot care demonstrations, and continued with checking blood sugar levels to residents. In addition, residents also received leaflets about diabetic foot care, with these leaflets it is hoped that residents can carry out foot care independently and correctly.